Assyrian Colonies in Cappadocia - Orlin, Louis L. (1970)
Gld. 64,-; Part I: The Old Assyrian Settlements and the Background of Cappadocian Trade; Part II: Political Relationships between the Assyrian Settlements and the Anatolian Principalities; Part III: Conclusions; the Assyrian kârû and wabârâtum were not colonies in an imperial sense; there was a system of shared sovereignty, or a parity-relationship between the Assyrians and the Anatolian principalities.